“You keep using that word”: gestural disruption as good vibes in higher education - Gagné, Ann; Patrie, Nicole; Lorenz, Danielle E. (My University, 2026)
This conversation piece centres around the use of the word disruption in different post-secondary spaces. More specifically, this piece discusses how disruption has impacted the work of inclusion in relation to accessibility, justice, and decolonization, as disruption is a term that is not well defined and yet commonly used in academic discourse. The authors speak to the pedagogical and research impact that gaps in understanding of disruption can and do function as praxis, and how these perforated understandings show up in different spaces in our institutions. The focus of the discussion is to identify spaces where relationality and holistic awareness has been lost and substituted for a feel-good type of disruption framing that does not allow for the needed discomfort or difficulty required for the work of inclusion to happen. Referencing pedagogical guidelines such as Universal Design for Learning (UDL) and current technologies that are prevalent in post-secondary spaces such as large language models (LLMs), the authors challenge readers to imagine what disruption is contextually in their work, beyond just using that word. The piece ends with an encouragement to move beyond symbolic gestures towards accessibility, justice, and decolonization to real change, and the hope that can accompany change in post-secondary spaces.
Keywords: disruption; decolonization; justice; accessibility; praxis